Ten Years After Bariatric Surgery: Bad Quality of Life Promotes the Need of Psychological Interventions - Galli, Federica; Cavicchioli, Marco; Vegni, Elena; Panizzo, Valerio; Giovanelli, Alessandro; Pontiroli, Antonio Ettore; Micheletto, Giancarlo (Frontiers in Psychology, 2018)
Background: This study aims to evaluate long-term quality of life (QoL) and primary clinical outcomes, 10 years after biliointestinal bypass (BIB) surgery. It was expected that, although BIB might show encouraging primary outcomes, long term QoL could be significantly impaired. Methods: Ninety patients were contacted for a phone interview [age 41.0 ± 10.6 (mean ± SD) years, age-range 31-65 years]. QoL (by SF-36) and the clinical situation (by ad hoc questionnaire) were collected. Data were analyzed with SPSS 22. SF-36 scores were compared with Italian normative data from general and healthy population. We also compared primary clinical outcomes and SF-36 scores between patients who reported high and low levels of satisfaction with BIB. Results: Considering SF-36 results, patients showed significant impairments in QoL compared to general and healthy populations. Sixty-five percent would repeat the BIB. All patients showed at least one chronic adverse event. It occurred a significant decrease in pre-post co-occurrence rates of diabetes (χ2 = 18.41; p < 0.001) and hypertension (χ2 = 50.27; p < 0.001). Large and significant weight loss indexes (i.e., percent excess weight loss (%EWL); body mass index) were observed between pre-post intervention. Conclusion: BIB showed promising primary clinical outcomes (i.e., hypertension, diabetes, and weight loss). However, subjects reported a significant impairment in all SF-36 domains. Ad hoc psychological interventions should be implemented to ameliorate the quality of life of these patients.